SCURRENT STATUS OF GRADUATE EDUCATION UNIT AND IMPROVEMENT PLAN - Barrientos Jiménez, Elsa Julia (2014)
Research carried out a diagnostic analysis of the Postgraduate Education Unit, considering tha differences, proposes a plan for improvement. The plan includes eight variables studied, taking into account their peculiarities in each.